Global burden of major gastrointestinal cancers and its association with socioeconomics, 1990–2019 - Hong, Mei-Zhu; Li, Jing-Mao; Chen, Zhi-Jian; Lin, Xiao-Yun; Pan, Jin-Shui; Gong, Li-Li (Frontiers in Oncology, 2022)
BACKGROUND To understand the impact of common cancers of the gastrointestinal tract and help to formulate evidence-based policy, we evaluate the relationship between the burden of GI tract cancers and socioeconomics. METHODS Data on GI tract cancer burden were obtained from the Global Burden of Disease (GBD) 2019 including mortality and incidence rates. According to the Socio-demographic Index (SDI) level, country and territory, and sex, etc, the data were further stratified. The association between the burden of GI tract cancer and socioeconomics, indicated by SDI, was described. Uncertainty analysis was estimated using bootstrap draw. RESULTS In 2019, five major cancers of the gastrointestinal tract led to an age-standardized incidence rate (ASIR) of 61.9 (95% CI 56.1–67.6) per 100 000 person-years. From 1990 to 2019, five common tumors of the gastrointestinal tract related age-standardized death rates (ASDRs) decreased by −22.7% (−31.1 to −13.5). For the five common tumors, ASIRs and ASDRs were both higher in males than those in females. Globally, Mongolia, and several East Asia countries exhibited the highest ASIRs in 2019. The high SDI, and high-middle SDI locations recorded the highest incidence rate and death rate of colon and rectum cancer and pancreatic cancer. On the contrary, the low-middle SDI, and low SDI locations possessed the highest incidence rate and death rate of stomach cancer and esophageal cancer. CONCLUSION There is a profound association between socioeconomics and burden of common cancers of the gastrointestinal tract. It would be helpful for the high SDI, and high-middle SDI locations to pay special attention to the screening of colon and rectum cancer and pancreatic cancer while the low-middle SDI, and low SDI locations should pay more attention to the screening of stomach cancer and esophageal cancer.